PENGGUNAAN DEOXYRIBO NUCLEIC ACID PADA PROSES KLONING EMBRIO MANUSIA DALAM PERSPEKTIF HUKUM ISLAM - Rizka, Rizka (Profetika Jurnal Studi Islam, 2013)
The use of the Deoxyribo Nucleic Acid (DNA) in the human embryo cloningis definitely a great invention of the centuries, yet the impact of its utilization bringsmore complicated problems. It is because the DNA can be taken from desired persons.It surely will lead to the problematical issues due to future offspring pedigree. It will behard to find out whose kids these cloning babies? Therefore, the law will be messed upwith things related to birth certificate and inheritance right. Even though the cloninguses the similar method with the IVF, it uses other cells but sperm. These cells bringother people?s DNA information with them therefore the children produced by thismethod will copy all the characteristics of the owners even without the help of penetrationbetween their parents. Hence it can be said that, in making a baby, woman does notneed man and marriage anymore. The reasons behind this human cloning inventionare to make perfect offspring that are far more intelligent, good looking, healthier,stronger, and perfectly same with the owner of the DNA. Embryo cloning, however, isthe sort of intervention of Allah creation. It means that people who involving in cloningprocess deny the Almighty of Allah. Is this the playing of Allah?s creation? How theIslamic laws see this phenomenon and give legal fatwa on the utilization of DNA incloning human embryo? How the National Laws of Indonesia sees this case? Because itseems that the national regulation in Indonesia is still not firm against the geneticengineering problems.Key words: cloning, deoxyribonucleic acid, embryoPenggunaan Deoxyribonucleic Acid (DNA) pada kloning embrio manusiaadalah penemuan besar sepanjang masa, namun masalah penggunaan DNA pada proseskloning embrio, merupakan masalah yang rumit, karena DNA bisa diambil dari siapasaja yang diinginkan. yang bisa membuat permasalahan bagi silsilah keturunannyakelak. Anak siapa?Keturunan siapa?hingga mempersulit dalam pembuatan aktekelahiran, hak waris, sehingga dapat mengacaukan hukum yang telah berlaku. Denganmetode yang hampir sama dengan bayi tabung, cloning menggunakan sel selain sperma.Sel ini yang berisi informasi DNA dari makhluk yang lain, kemudian hasilnya jugadimasukkan kembali ke induknya. Sehingga menciptakan anak tanpa membutuhkanlaki-laki,tanpa perkawinan juga. Kloning manusia diciptakan untuk alasan memperbaikiketurunan; supaya lebih cerdas, rupawan lebih sehat, lebih kuat dan menyamai dariDNA yang di kloning tersebut. Kloning embrio dengan mengambil DNA orang lainadalah bentuk intervensi dari penciptaan Allah, padahal Allah adalah Sang PenciptaIndoyangmaha sempurna. Apakah ini termasuk mempermainkan Ciptaan Allah?BagaimanaHukum Islam memberikan fatwa hukum pada penggunaan DNA untuk cloning embriomanusia dan bagaimana tinjauan dari Hukum yang berlaku di Indonesia yang hinggasekarang belum tegas terhadap banyak permasalahan rekayasa genetika.Kata kunci: kloning, deoxyribonucleic acid, embrio